In vivo survival and differentiation of Friedreich ataxia iPSC‐derived sensory neurons transplanted in the adult dorsal root ganglia. (18th March 2021) - Viventi, Serena; Frausin, Stefano; Howden, Sara E.; Lim, Shiang Y.; Finol‐Urdaneta, Rocio K.; McArthur, Jeffrey R.; Abu‐Bonsrah, Kwaku Dad; Ng, Wayne; Ivanusic, Jason; Thompson, Lachlan; Dottori, Mirella
Abstract: Friedreich ataxia (FRDA) is an autosomal recessive disease characterized by degeneration of dorsal root ganglia (DRG) sensory neurons, which is due to low levels of the mitochondrial protein Frataxin. To explore cell replacement therapies as a possible approach to treat FRDA, we examined transplantation of sensory neural progenitors derived from human embryonic stem cells (hESC) and FRDA induced pluripotent stem cells (iPSC) into adult rodent DRG regions. Our data showed survival and differentiation of hESC and FRDA iPSC‐derived progenitors in the DRG 2 and 8 weeks post‐transplantation, respectively. Donor cells expressed neuronal markers, including sensory and glial markers, demonstrating differentiation to these lineages. These results are novel and a highly significant first step in showing the possibility of using stem cells as a cell replacement therapy to treat DRG neurodegeneration in FRDA as well as other peripheral neuropathies. Abstract : This study is the first to describe transplantation of dorsal root ganglia (DRG) sensory neural progenitors derived from human pluripotent stem cells (hPSC) into adult rodent DRG tissue. Donor cells differentiated to neurons and glia in vivo and expressed DRG sensory markers. These findings are highly significant in supporting stem cell‐based therapies for treating peripheral DRG neuropathies, including Friedreich ataxia. Figure created using BioRender.com